“Efecto de cuatro dosis fosfonato de potasio en el cultivo de pepinillo híbrido em american slicer 160 F1 HyB, en la provincia de Lamas” - Ramos Leiva, Roiser Horacio (2014)
The present intitulad research work effect of four doses of Phosphonate of Potassium in the cultivation of hybrid cucumber EM AMERICAN SLICER 160 F1 HyB, in the Province of Lamas, took effect with the purpose of evaluating the effect of four doses of Phosphonate of Potassium in the production of the cultivation of cucumber (Cucumis sativus L.), was used for the statistical design of randomized complete block, with three blocks and tour treatments, whose studied variables were: Height of plants, weight of fruits, length of fruit, diameter of fruit, number of fruits for plant, performances of fruits in t.ha -1 and economic analysis. The results obtained in the present investigation, indicate that the treatment T3 (O. 75 l.ha·1 of Phosphonate of Potassium), obtained the best results in relation to the studied variables, because the Phosphorate and Potassium induced physiological that promoted the growth, plant development, formation of fruits increasing the size and the weight. The treatment T3 (0.75 l.ha·1 of Phosphonate of Potassium) obtained the bigger value of B/C with 1.82 and a benefit net of SI. 8723.32, follow of the treatments T2 (0.5 l.ha -1 of Phosphonate of Potassium), T4 (1 l.ha·1 of Phosphonate of Potassium), T1 (0.25 l.ha·1 of Phosphonate of Potassium) and TO (Witness) who's obtained values BIC of 1.37; 1.09; 0.58 and 0.21 and benefit net of SI. 6036.77, SI. 4961.91, S/. 2108.42 and SI. 651.42 respectively. Key Words: Cucumber, hybrid EM AMERICAN SLICER 160 F1 HyB, phosphonate, potassium, synergism, antagonism.